Clinical and epidemiological profile of patients with mental disorders in a specialized outpatient clinic and its role in the psychosocial care network - Camargos, Gláucio Silva; Garcia, Mateus Afrânio Von Ancken; de Almeida, Carolina Andreazza; Lopes, Angélica Marta; Borghi, Fábio Aparecido; de Araújo Filho, Gerardo Maria; de Mattos, Luíz Carlos; Brandão, Cinara Cássia (Frontiers in Psychiatry, 2024)
Introduction: Mental health disorders (MHD) are responsible for much impairment of quality of life in Brazil and worldwide. early diagnosis and effective treatment strategies are required due to the heterogeneous symptoms and multifactorial etiology. Methods: A descriptive retrospective observational study was performed aiming to characterize the clinical and psychiatric profiles of patients with MHD accompanied in a Brazilian public tertiary psychiatric outpatient clinic, which is a reference health service for more than 2 million inhabitants. Predominant clinical and sociodemographic aspects of patients were evaluated between March 2019 and March 2021. Results: A total of 8384 appointments were analyzed. The majority of patients were female and the mean age was 45 years old. Generalized Anxiety Disorder (GAD) was the most common MHD. The prevailing symptoms were sadness, anxiety and irritability with the most prescribed medications being selective serotonin reuptake inhibitors. Conclusion: The epidemiological characterization of mental disorders in specialized mental health outpatient clinics provides evidence for the establishment of more specific protocols and advocates a dimensional transdiagnostic approach as an aid to public mental health services.